2019
DOI: 10.1108/jibr-08-2018-0204
|View full text |Cite
|
Sign up to set email alerts
|

Operating performance of acquirers after acquisition: evidence from India

Abstract: Purpose The purpose of this paper is to examine the operating performance of Indian using difference-in-difference (DD) methodology. It, further, examines whether there is a difference in the operating performance of acquirers doing partial and full acquisitions. Design/methodology/approach Four different benchmark criteria are used to select control firms, namely, size, size and industry, size and leverage, and size and book-to-market ratio. To measure the operating performance, return on assets (ROA) is ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The study also found that profitability and liquidity of acquiring firms had a positive impact on the merger, but there was no impact of the merger on solvency position of acquiring firms. Dixit (2019) examined the operating performance, using difference-in-difference methodology, to empirically test performance differences, among acquirers who pursued partial and full acquisition using Indian M&A. It was found that Indian acquiring firms realized no change in accounting measures, while their operating performance significantly reduced in the post-acquisition period for full acquirers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study also found that profitability and liquidity of acquiring firms had a positive impact on the merger, but there was no impact of the merger on solvency position of acquiring firms. Dixit (2019) examined the operating performance, using difference-in-difference methodology, to empirically test performance differences, among acquirers who pursued partial and full acquisition using Indian M&A. It was found that Indian acquiring firms realized no change in accounting measures, while their operating performance significantly reduced in the post-acquisition period for full acquirers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While there are instances where M&A benefits shareholders, it tends to favour the target firm's shareholders (Ang, Daher, & Ismail, 2019). Conversely, acquirer shareholders often experience adverse effects following the merger announcement (Dixit, 2020). Moreover, previous studies have suggested that excessive premiums may be paid in merger and acquisition transactions, leading to overvaluation of the transaction value .…”
Section: The Transaction Price Of Mergers and Acquisitions And Corpor...mentioning
confidence: 99%
“…Mergers and acquisitions (M&A) is a process by which a company acquires control of another company, for instance, by buying or taking over shares. M&A mainly includes horizontal M&A [1][2][3][4] , vertical M&A, and mixed M&A [5][6][7] . There are many motivations for M&A, including strengthening the integrative effect of enterprise supply chain, achieving the synergistic effect of M&A, and expanding the market.…”
Section: A Theoretical Overview 1the Concept and Types Of Mergers And...mentioning
confidence: 99%